Efficient routing mechanism for neighbour selection using fuzzy logic in wireless sensor network. (September 2021) - Ramkumar, K.; Ananthi, N.; Brabin, D. R. Denslin; Goswami, Puneet; Baskar, M.; Bhatia, Komal Kumar; Kumar, Harish
Highlights: The article is focused on improving the performance of data transmission in wireless sensor network. The highlights of the research are as follows. Active relay nodes are identified with fuzzy logic and utility factor. Coverage distance is measured with Received Signal Strength (RSS) The fuzzy inference system selects the next relay node according to the coverage distance, energy and utility factor and bandwidth availability factors. By choosing relay node according to the above mentioned factors, the data transmission performance is improved. Abstract: Numerous sensor nodes are getting utilized in the field of Wireless Sensor Network (WSN) for complex communication. In the recent scenario, there is a lack in the number of sensor node placement with less sensing and communication capabilities. There is less involvement with the characteristics of sensor nodes for direct communication with remote nodes. During the communication, sensor data are communicated to the sink with the help of sensor hubs. Therefore to improve the performance of QoS, routing in the integration of relay node selection plays an important role in WSN. In this paper, we propose Fuzzy based Relay Node Selection and Energy Efficient Routing (FRNSEER) make the routing more efficient by selecting the effective relay node while communicating with the sink node. For selecting the sink node, fuzzy rules are used where active relay nodes are selected as the outcome. The active relay node selection helps to determine the better energy and utility factor during the transmission process. To make better communication between the relay node and the sink node, sensor hubs are used with a lower energy expenditure schedule with expected functions of neighbor/working nodes. In the performance analysis, the proposed mechanism will perform better in terms of packet rate with low energy consumption compared to the existing algorithms such as Fuzzy-based Hyper Round Policy (FHRP) and Neural Network-based Localisation Scheme (NNBLS). Graphical abstract: Image, graphical abstract